Connection between Behavioral Intention, perceived Usefulness, and perceived Ease of Use for Indonesian GoPay E-Wallet Users - Elza Nur Zaskia; Arinal Muna (Cita Konsultindo Research Center, 2024)
The use of mobile payments has experienced rapid growth, particularly in adopting GoPay as a transactional tool. This study aims to investigate the relationship between perceived usefulness (PU), perceived ease of use (PEOU), and behavioral intention (BI) among GoPay users in Indonesia. Using a quantitative research method with descriptive analysis and snowball sampling techniques, data were collected from 104 GoPay users across Indonesia. The data were analyzed using the Partial Least Square (PLS) program version 4.0. The findings indicate that both perceived ease of use and behavioral intention have a positive and significant impact on perceived usefulness. Additionally, perceived ease of use positively and significantly influences behavioral intention. The interaction between perceived ease of use and behavioral intention further moderates and strengthens the relationship between perceived ease of use and perceived usefulness. These results suggest that the ease of use of GoPay encourages users to have a stronger intention to use the application, which, in turn, enhances their perception of its usefulness.